Above 40% of Polish children and young adults with type 1 diabetes achieve international HbA1c target ‐ results of a nationwide cross‐sectional evaluation of glycemic control: The PolPeDiab HbA1c study. Issue 7 (4th August 2021) - Szadkowska, Agnieszka; Baranowska‐Jaźwiecka, Anna; Michalak, Arkadiusz; Jarosz‐Chobot, Przemysława; Myśliwiec, Małgorzata; Głowińska‐Olszewska, Barbara; Szypowska, Agnieszka; Nazim, Joanna; Mazur, Artur; Szalecki, Mieczysław; Skowrońska, Bogda; Kucharska‐Zubkiewicz, Agnieszka; et al.
Abstract: Background: Youth with type 1 diabetes (T1D) (16–18 y.o.) present worst disease control of all age groups and need structured interventions. Those should be based on unbiased, national‐scale outcomes, which have not yet been successfully assessed in Poland. Objective: To evaluate the glycemic control in young patients with T1D in Poland. Method: All pediatric diabetes care centers and the nine largest centers for adults with T1D were invited to this cross‐sectional study, conducted in March 2018. Eligibility was defined as age ≤ 30 years and diabetes duration ≥1 year. Blinded samples of capillary blood and clinical questionnaires were sent to coordinating center, where HbA1c was measured by high‐pressure liquid chromatography. Results: Nine adult and 25/28 pediatric centers participated, providing data for 1255 patients (50.8% males), mean age 12.3 years (95%CI:12.1–12.6) for children and 23.2 years (22.9–23.6) for adults; mean diabetes duration 7.1 years (6.8–7.3). This covered ~8% of pediatric population and 2% of 18–30‐years‐olds with T1D. Mean HbA1c was comparable between children and adults (57 mmol/mol [7.4%], 95%CI:56‐57 mmol/mol [7.3–7.4%] vs. 57 mmol/mol [7.4%], 95%CI:56–60 mmol/mol [7.3–7.6%], p  = 0.1870). Overall, 45.2% of patients achieved ISPAD target (<53 mmol/mol [<7.0%]). During the month preceding the study, 0.9% of patients experienced severe hypoglycemia and 0.4% suffered ketoacidosis. HbA1c was related to the method of insulin therapy, continuous glucose monitoring use and body weight ( p  < 0.0001). Conclusions: In Polish children and young adults with T1D glycemic control expressed as HbA1c is promising in the light of ISPAD guidelines. Our results confirm the known associations between better glycemic control and the use of new technologies and maintaining optimal body weight.